Ethical Leadership as Process: A Conceptual Proposition. (2nd November 2019) - Shakeel, Fahad; Kruyen, Peter Mathieu; Van Thiel, Sandra
Abstract : This conceptual study proposes that ethical leadership is studied through a processual lens. The study develops different models of ethical leadership as a process. Multiple constructs of ethical leadership from the literature are compared and used to develop these models, including a timeline of ethical leadership, a two-dimensional quadrant, and concentric circles of ethical leadership. The models provide a new perspective into the function and interdependency of the constituent parts to study ethical leadership as a process. The research agenda provides a roadmap for how these assumptions can be tested empirically, by looking into the external orientation of leaders— for example, through administering a broader ethical leadership measurement tool. This study calls for future research to test this assumption empirically, explore antecedent factors, and study various historically important leaders through their actions and decisions to test if they followed a leadership development path in accordance with the proposed model.